Real‐Time SWMF at CCMC: Assessing the Dst Output From Continuous Operational Simulations. Issue 10 (15th October 2018) - Liemohn, Mike; Ganushkina, Natalia Yu.; De Zeeuw, Darren L.; Rastaetter, Lutz; Kuznetsova, Maria; Welling, Daniel T.; Toth, Gabor; Ilie, Raluca; Gombosi, Tamas I.; van der Holst, Bart
Abstract: The ground‐based magnetometer index of Dst is a commonly used measure of near‐Earth current systems, in particular the storm time inner magnetospheric current systems. The ability of a large‐scale, physics‐based model to reproduce, or even predict, this index is therefore a tangible measure of the overall validity of the code for space weather research and space weather operational usage. Experimental real‐time simulations of the Space Weather Modeling Framework (SWMF) are conducted at the Community Coordinated Modeling Center (CCMC). Presently, two configurations of the SWMF are running in real time at CCMC, both focusing on the geospace modules, using the Block Adaptive Tree Solar wind‐type Roe Upwind Solver magnetohydrodynamic model, the Ridley Ionosphere Model, and with and without the Rice Convection Model. While both have been running for several years, nearly continuous results are available since April 2015. A 27‐month interval through July 2017 is used for a quantitative assessment of Dst from the model output compared against the Kyoto real‐time Dst. Quantitative measures are presented to assess the goodness of fit including contingency tables and a receiver operating characteristic curve. It is shown that the SWMF run with the inner magnetosphere model is much better at reproducing storm time values, with a correlation coefficient of 0.69, a prediction efficiency of 0.41, and Heidke skill score of 0.57 (for a −50‐nT threshold). A comparison of real‐time runs with and without the inner magnetospheric drift physics model reveals that nearly all of the storm time Dst signature is from current systems related to kinetic processes on closed magnetic field lines. Plain Language Summary: As society becomes more dependent on technologies susceptible to adverse space weather, it is becoming increasingly critical to have numerical models capable of running in real time to nowcast/forecast the conditions in the near‐Earth space environment. One such model is available at the Community Coordinated Modeling Center and has been running for several years, allowing for an assessment of the quality of the result. Comparisons are made against globally compiled index of near‐Earth space storm activity, including numerous statistical quantities and tests. The skill of the model is remarkable, especially when a few hours after each of the cold restarts of the model are removed from the comparison. It is also shown that a global model alone is not that good at reproducing this storm index; a regional model for the inner part of geospace is necessary for good data‐model agreement. Key Points: The SWMF model has been running in experimental real‐time mode at CCMC for several years, and all saved output is available The comparison against real‐time Dst is quite good, especially when a few hours after cold restarts are removed from the comparison It is necessary to include an inner magnetospheric drift physics model to reproduce Dst; a real‐time run without one does much worse